HIV Data to Care—Using Public Health Data to Improve HIV Care and Prevention. (1st September 2019) - Sweeney, Patricia; DiNenno, Elizabeth A.; Flores, Stephen A.; Dooley, Samuel; Shouse, R. Luke; Muckleroy, Stacy; Margolis, Andrew D.
Abstract : Background: "Data to Care" (D2C) is a public health strategy that uses surveillance and other data to improve continuity of HIV care for persons with HIV (PWH) by identifying those who are in need of medical care or other services and facilitating linkage to these services. The primary goal of D2C is to increase the number of PWH who are engaged in care and virally suppressed. Methods: Data to Care can be implemented using several approaches. Surveillance-based D2C is usually initiated by health departments, using HIV surveillance and other data to identify those not in care. Health care providers may also initiate D2C by identifying patients who may have fallen out of care and working collaboratively with health departments to investigate, locate, and relink the patients to medical care or other needed services. Results: Although D2C is a relatively new strategy, health department D2C programs have reported both promising results (eg, improved surveillance data quality and successful linkage to or re-engagement in care for PWH) and challenges (eg, incomplete or inaccurate data in surveillance systems, barriers to data sharing, and limitations of existing data systems). Conclusions: Data to Care is expected to enable health departments to move closer toward achieving national HIV prevention goals. However, additional information on appropriate implementation practices at each step of the D2C process is needed. This JAIDS Special Supplement explores how CDC funding to state health departments (eg, technical assistance and demonstration projects), and partnerships across federal agencies, are advancing our knowledge of D2C.